Estudo mecânico de flexão, ex-vivo, de fêmures suínos osteotomizados, estabilizados com dois tipos de haste de poliamida 12 - Almeida, Juliana Scarpa da Silveira; Garcia, Débora de Oliveira; Bortholin, Renato Camargo; Razzino, Carlos Amaral [UNESP]; Honsho, Cristiane dos Santos; Dias, Fernanda Gosuen Gonçalves; de Mattos-Junior, Ewaldo; Dias, Luis Gustavo Gosuen Gonçalves [UNESP] (FapUNIFESP (SciELO), 2017)
Long bone fractures are commonly in surgery routine and several bone imobilization techniques are currently available. Technological progress has enabled to use low cost materials in surgical procedures. Thus, the aim of this study was to evaluate the applicability of polyamide 12 rods, solid and hollow in swine femurs, comparing them through flexion strength. This study had as second aim to fix the locking errors, commom place in interlocking nails, once polyamide 12 allows perforation in any direction by orthopaedic screw. Six groups were used: G1 - eight whole swine femurs; G2 - eight whole swine femurs with drilled medullary canal; G3 - two solid polyamide 12 rods; G4 - two hollow polyamide 12 rods; G5 - eight osteotomized drilled swine femurs with a solid polyamide 12 rod implanted in the medullary canal and locked by four 316L stainless steel screws; and G6 - similar to G5 but using hollow rods instead of solid ones. No significant differences were observed for the modulus of rupture between solid and hollow rods, demonstrating that both rods had similar performances. These results led to the speculation that the addition of other polymers to the hollow rods could increase their strength and thus the bone-implant system. Furthermore, the comparison between G1, G5 and G6 could be analyzed using the finite element method in future. New polymeric materials may be developed based on the data from this study, strengthening the bone-implant system and making possible screws to be placed in any direction, nullifying the detrimental forces on the fracture site.
Mechanical flexural ex vivo study of osteotomized swine femurs stabilized with two types of polyamide 12 rods
Keywords: Biomechanical test; Implants; Interlocking nail; Laser sintering; Prototyping